(3GdCSaGQ Yf hLhg eNOQGJ GdOQ GdeNJGQs - (3YHO GdQMef Hf MSf GdLHQJj GdeUQj GdMfaj,J (B1237 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ Edi dWa QHg GdNai MSf Hf MSf GdLHQJi GdMfai Cfg bO hbY ai YHGQI GdOQ GdeNJGQ TQM JfhjQ GdCHUGQ s
(3BNQgG (B:s
(3hCMcGegG ePchQI ai eMdgG eaUdI adG CWjd HgG s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B304 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B133s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfajs